2015
DOI: 10.1504/ijhfe.2015.073002
|View full text |Cite
|
Sign up to set email alerts
|

Applying the chronicle workshop as a method for evaluating participatory interventions

Abstract: Despite the growing interest for process evaluation in participatory interventions, studies examining specific methods for process evaluation are lacking. In this paper, we propose a new method for process evaluation--the Chronicle Workshop. The Chronicle Workshop has not previously been used in intervention studies. The method was tested in three small and medium-sized companies. Four to six employees participated in each Chronicle Workshop, which was the last activity of the participatory preventive interven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…In a study by Aust et al (2010), occupational health consultants suggested that the focus on participation had been problematic as employees were poorly equipped to manage the process and line managers felt unsure about their role. Framke and Sørensen (2015) reported that the opportunity to fit the intervention to the organization was perceived to be a strength and Poulsen et al (2015) found that the pressure to bill time on projects prevented employees from engaging with the intervention. reported that their SME-focused intervention did not fare well in an organization where people worked across different shifts because communication and participation was limited across shifts.…”
Section: What Do We Know?mentioning
confidence: 99%
“…In a study by Aust et al (2010), occupational health consultants suggested that the focus on participation had been problematic as employees were poorly equipped to manage the process and line managers felt unsure about their role. Framke and Sørensen (2015) reported that the opportunity to fit the intervention to the organization was perceived to be a strength and Poulsen et al (2015) found that the pressure to bill time on projects prevented employees from engaging with the intervention. reported that their SME-focused intervention did not fare well in an organization where people worked across different shifts because communication and participation was limited across shifts.…”
Section: What Do We Know?mentioning
confidence: 99%
“…To gain insight into the participants’ use and adaption experiences with the visualization object, we conducted semi‐structured interviews, observations and chronicle workshops (CWs; Limborg & Hvenegaard, ; Poulsen, Ipsen & Gish, ), followed by a cross‐case analysis (Miles, Huberman, & Saldana, ). Data collection was conducted eight times during the intervention period of 6 to 9 months.…”
Section: Methodsmentioning
confidence: 99%
“…The answers for questions 2 and 3 are mapped on the timeline. The outcome of the CW is a summary view of intervention‐related results and influencing factors (Poulsen et al, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(Nielsen and Abildgaard, 2013: 285–286) In practice, contexts are diverse and are studied in a number of different ways, and, as a result, establishing general patterns of how combinations of organizational interventions and contexts produce (or fail to produce) certain effects is still challenging (Daniels et al, 2017; Havermans et al, 2016). However, as an example of an important contextual factor, Poulsen et al (2015) reported that the participants in their POI study experienced a pressure to bill time on work projects that deterred employees from engaging in the intervention. In relation to concurrent contextual events, Nielsen et al (2006) demonstrated how the differences in the context and implementation of a health promotion initiative led to markedly different effects in the targeted workplaces.…”
Section: Introductionmentioning
confidence: 99%